LEAF ACCLIMATION OF ROBUSTA COFFEE TREES TO PHOTOSYNTHETIC EFFICIENCY OF SHADE-GROWN CONDITIONS IN RUBBER-COFFEE INTERCROPPING SYSTEMS - Rawee Chiarawipa; Buntarika Kulasin; Monsuang Rueangkhanab (Journal of Animal and Plant Sciences, 2025)
Robusta coffee plant is typically grown under the canopy of shade-providing trees in lowland areas of tropical regions. The study aimed to assess the leaf acclimation and the photosynthetic capacity of Robusta coffee trees under different levels of shade provided by rubber trees in rubber-coffee intercropping systems. The efficiency of photosynthetic traits was studied in 5-year-old Robusta coffee trees intercropped under four different levels of rubber tree shades (SH1 – slight shade, SH2 – moderate shade, SH3 – high shade, and SH4 – heavy shade). The results showed that the SH3 and SH4 (45% and 15% transmission) plantations had lower light transmission than the SH1 and SH2 (80% and 70% transmission) plantations. There was no statistical difference in canopy temperatures among the Robusta coffee trees under the SH2 (30.46 °C), SH3 (30.19 °C), and SH4 (29.85 °C) plantations. The chlorophyll fluorescence (Fv/Fm) ranged from 0.770 to 0.799 showing similar values in SH2, SH3, and SH4 plantations. The greatest total chlorophyll content (Chltotal) values were recorded in SH3 and SH4 plantations. Additionally, gas-exchange rates in Robusta coffee trees were higher under the slight shade (SH1) condition, with optimal performance at higher light intensity (1,200 μmol/m2/s) and higher temperatures at 35°C. The net photosynthetic rate (Pn) response curves exhibited dominance in the SH1 and SH2 plantations, maintaining a similar pattern throughout all light-saturating conditions. The highest values of photosynthetic capacity under biochemical limitations (Pmax, Is, Vc,max, Jmax, and TPU) were also observed in both SH1 and SH2 plantations, which were 61.37%, 56.29%, 45.44%, 56.84% and 45.84%, respectively higher than those of SH3 and SH4 plantations. According to the results, optimizing light transmission could potentially lead to more efficient Robusta coffee’s photosynthetic capacity as an intercropping condition. This study suggests that the Robusta coffee tree could adapt to fluctuating light transmission, more than 50% rubber-shaded conditions could ultimately lead to reduced photosynthetic efficiency, resulting in slower growth and lower yield potential in a rubber-coffee intercropping system.
Keywords: Chlorophyll content; leaf photosynthetic capacity; rubber agroecology; rubber tree age; shade acclimation